Clinico-epidemiological study on metal-induced contact dermatitis from North India - Singh, Khushman; Gupta, Sunil Kumar; Gupta, Veenu; Brar, Sukhmani Kaur (Journal of Pakistan Association of Dermatologists, 2016)
Objective To determine the prevalence of metal sensitization and different clinical patterns in suspected patients of metal induced contact dermatitis. Â Methods This was an epidemiological study during which a total of 100 patients suspected and provisionally diagnosed as having contact dermatitis to metals were subjected to a patch test with Indian Standard Battery developed by CODFI (Contact and Occupational Dermatoses Forum of India). Results were read after 48hrs of application and a second reading, if required, was taken after 72-96hrs. Â Results Most of the patients in this series presented with hand eczema (40%), which was followed by dermatitis localized to site of contact with metal (20%) and facial dermatitis including eyelid dermatitis (15%). Twenty-seven patients showed positive reactions to metal allergens. Cross-sensitivity was low and three patients or 11.11% showed sensitization to two metal allergens. No patient showed sensitization to all the three metals. Â Conclusion Nickel was the commonest metal allergen identified and it was relevant in 100% of the cases. It showed a strong female preponderance. Patch testing is hence a helpful diagnostic aid in identifying the agents responsible for contact dermatitis and a sincere effort should be made to determine clinical relevance of the test results in every case.